Short-Term Global Instability and Genu Recurvatum Outcomes of Revision Total Knee Arthroplasty with Rotating-Hinged Knee Prosthesis - Sripadet, Pichate; Khuangsirikul, Saradej; Heebthamai, Danai; Phruetthiphat, Ong-Art; Chotanaphuti, Thanainit (Journal of Southeast Asian Orthopaedics, 2023)
Purpose: Primary revision total knee arthroplasty (TKA) is associated with bone loss and ligamentous insufficiency. After TKA, patients may have global knee instability or genu recurvatum and require revision TKA with a rotating-hinged knee (RHK) prosthesis. However, several studies have reported variable outcomes. This study aimed to: 1) evaluate the outcomes of revision TKA with an RHK prosthesis; and 2) compare the outcomes and satisfaction of patients with global instability and genu recurvatum following revision TKA. Methods: The cases of 18 patients (mean age, 71 ± 8.5 years; mean follow-up time, 24 months (range, 12–38 months) who underwent revision TKA with an RHK prosthesis in 2015–2018 were retrospectively reviewed. Patients were further classified into the global instability group (n=11), those who were diagnosed with periprosthetic joint infection (8 patients), TKA dislocation (2 patients), and periprosthetic fracture with a complete tear of the medial collateral ligament (1 patient); and the genu recurvatum group (n=7). Clinical evaluations were performed preoperatively, at 1 year postoperative, and at the last follow-up. Outcomes were assessed using the Knee injury and Osteoarthritis Outcome Score (KOOS), pain visual analog scale (VAS), range of motion (ROM), complications, and radiographic data. Patient satisfaction was assessed at the 1-year follow-up using a self-administered scale. Results: Overall, the mean KOOS at the 1-year follow-up was significantly improved versus preoperative (71.39 ± 8.65 vs. 22.56 ± 11.58, p<0.001). The mean 1-year postoperative KOOS (50 vs. 47, p=0.028), surgical satisfaction score (p=0.005), home activity satisfaction score (p=0.0029), and recreational activity satisfaction score (p=0.024) were significantly higher in the global instability versus genu recurvatum group, whereas the mean pain VAS score was significantly higher in the global instability versus genu recurvatum group (6 vs. 4, p=0.037). The mean ROM improved from 30° to 90° in the global instability group and from -20° to 0° in the genu recurvatum group. No surgical complications or signs of prosthesis loosening were observed. Conclusions: Revision TKA with an RHK prosthesis showed better functional outcomes in patients with global instability versus genu recurvatum. Furthermore, patients with global instability showed higher satisfaction with surgery, home, and recreational activities than those with genu recurvatum.